Ruchy społeczne osób starszych i działalność pokoleniowa seniorów w usieciowionych miastach. Perspektywa polsko-francuska = Social movements of the elderly and generational activities of seniors in networked cities: a Polish-French perspective - Bogalska-Martin, Ewa; Wachowiak, Anna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The median age of Europe`s societies is increasing at an unprecedented pace, leading to a growing proportion of senior citizens in the total population. Social policies in various countries are evolving to meet the challenges posed by an aging population. Central to these policies is the principle of equal treatment for seniors, a cornerstone of the broader vision of an inclusive Europe, characterised by open societies.
Keywords: inkluzywne społeczeństwo; usieciowione miasto; aktywne starzenie się; ruchy społeczne seniorów; pokolenie seniorów; inclusive societies; networked cities; active ageing, seniors` movements; senior generation